2017
DOI: 10.1021/acs.jafc.7b03690
|View full text |Cite
|
Sign up to set email alerts
|

New Method To Produce Kokumi Seasoning from Protein Hydrolysates Using Bacterial Enzymes

Abstract: In the present study, we demonstrate a novel use for a commercially available glutaminase that can be used as a γ-glutamyltranspeptidase in kokumi seasoning production. Soy protein and gluten were hydrolyzed using a protease isolated from Bacillus licheniformis. The resulting protein hydrolysates were γ-glutamylated with a γ-glutamyltranspeptidase, which is sold as a glutaminase from Bacillus amyloliquefaciens, to produce kokumi seasonings. For γ-glutamylation of soy protein hydrolysate, glutamine was added to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 24 publications
1
26
0
Order By: Relevance
“…27 Glutaminase SD-C100S prepared from B. amyloliquefaciens is sold as glutaminase; nonetheless, it has been reported that it could be used to catalyze the transpeptidation reaction. 12 To validate the composition of the commercial glutaminase SD-C100S, LC−MS/MS was used to identify its peptide fragments based on the in-solution trypsin digestion method. As shown in Table 1, 11 identified peptides were matched with α-amylase of B. amyloliquefaciens (D3Y3H2, 58.2 kDa), and the coverage was 14%, whereas 18 identified peptides were matched with GGT (A0A4V7TPB1, 64.2 kDa) from B. amyloliquefaciens, and the coverage was 27%.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…27 Glutaminase SD-C100S prepared from B. amyloliquefaciens is sold as glutaminase; nonetheless, it has been reported that it could be used to catalyze the transpeptidation reaction. 12 To validate the composition of the commercial glutaminase SD-C100S, LC−MS/MS was used to identify its peptide fragments based on the in-solution trypsin digestion method. As shown in Table 1, 11 identified peptides were matched with α-amylase of B. amyloliquefaciens (D3Y3H2, 58.2 kDa), and the coverage was 14%, whereas 18 identified peptides were matched with GGT (A0A4V7TPB1, 64.2 kDa) from B. amyloliquefaciens, and the coverage was 27%.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Glutaminase SD-C100S prepared from B. amyloliquefaciens is sold as glutaminase; nonetheless, it has been reported that it could be used to catalyze the transpeptidation reaction . To validate the composition of the commercial glutaminase SD-C100S, LC–MS/MS was used to identify its peptide fragments based on the in-solution trypsin digestion method.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Protein hydrolysates are commercially available for food manufacturers and widely added to processed food to increase the complexity of umami taste in Japan. Therefore, we developed a new method to produce kokumi seasoning by γ-glutamylation of protein hydrolysates made by bacterial protease 22 .…”
Section: Utilization Of the Transpeptidation Activity Of Ggt To Synthmentioning
confidence: 99%